Influence of pre-heat treatment and different light-curing units on Vickers hardness of a microhybrid composite resin - Saade, E. G.; Bandeca, M. C.; Rastelli, Alessandra Nara de Souza [UNESP]; Bagnato, V. S.; Porto-Neto, S. T. (Pleiades Publishing, 2009)
The aim of this study was to evaluate the hardness of a dental composite resin submitted to temperature changes before photo-activation with two light-curing unite (LCUs). Five samples (4 mm in diameter and 2 mm in thickness) for each group were made with pre-cure temperatures of 37, 54, and 60°C. The samples were photo-activated with a conventional quartz-tungsten-halogen (QTH) and blue LED LCUs during 40 s. The hardness Vickers test (VHN) was performed on the top and bottom surfaces of the samples. According to the interaction between light-curing unit and different pre-heating temperatures of composite resin, only the light-curing unit provided influences on the mean values of initial Vickers hardness. The light-curing unit based on blue LED showed hardness mean values more homogeneous between the top and bottom surfaces. The hardness mean values were not statistically significant difference for the pre-cure temperature used. According to these results, the pre-heating of the composite resin provide no influence on Vickers hardness mean values, however the blue LED showed a cure more homogeneous than QTH LCU. © 2009 Pleiades Publishing, Ltd.
Keywords: Blue LEDs; Bottom surfaces; Composite resins; Cure temperature; Dental composite resins; Light curing; Light-curing units; Mean values; Photo-activated; Pre-heat treatment; Quartz tungsten halogen; Statistically significant difference; Temperature changes; Vickers; Curing; Dental composites; Heating; Oxide minerals; Quartz; Resins; Tungsten; Vickers hardness